Clinical Efficacy of Oral Administration of Finasteride at a dose of 2.5mg/Day in Women with Female Pattern Hair Loss - Niazi, Nuzha; Malik, Aisha; Khan, Farwa Nasir; Ishfaq, Rabia; Quratulain; Imtiaz, Aqsa (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find clinical efficacy of oral administration of finasteride at a dose of 2.5mg/day in women with female pattern hair loss. Study design: Descriptive cases series Place and duration of study: Department of Dermatology, Unit II, Mayo Hospital Lahore from 01-10-2019 to 31-03-2020. Methodology: A total of 137 cases were taken. Trichoscopy was performed at enrollment and after 5 months. At the standardized resolution of each image, ratio of terminal to vellus hair measured at two sites of the scalp. Clinical efficacy was determined as per operational definition at 5th month of treatment. Results: Patients ranged between 40-70 years of age with mean age of 49.5±6.9 years. Pre-menopause women were 99 (72.3%) while post-menopause were 38(27.7%). Mean duration of FPHL was observed 4.4±1.3 months. Out of 137 cases, 92 women (67.2%) belonged to Ludwig scale-I and remaining 45 women (32.8%) belonged to Ludwig scale-II. Clinical efficacy of finasteride 2.5mg/day was found in 85 women (62%). Stratification for age, duration of FPHL, menopause status, and baseline Ludwig scale was also carried out. Four to six months duration of FPHL, premenopausal women and lower Ludwig scale showed significant effect of finasteride (p <0.001, p=0.010 and p 0.003, respectively). Conclusion: In conclusion, the efficacy of administration of finasteride at a dose of 2.5 mg/day for patients with female pattern hair loss was recorded 62%, and it was also observed that finasteride revealed better effect on hair growth in patients having lower Ludwig score.